2000
DOI: 10.1515/cclm.2000.064
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iron Status with a New Fully Automated Assay for Transferrin Receptor in Human Serum

Abstract: Serum transferrin receptor is considered as a reliable marker of iron status particularly when iron deficiency is associated with chronic disorders such as inflammation, infection or malignancy. The present study aims to illustrate the performances of a new fully automated assay using immunonephelometry. The intra and between-assay precision was found to be very good (CVs < 4%). In healthy subjects there was no statistically significant difference between men and women. With a cut-off of 1.76 mg/l for diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…Kohgo et al and Allen et al [9,12] in their respective study, even though the former reported lower values and the latter higher sTfR values for each sex, did not find any significant difference in their mean sTfR as also seen in other related studies. [31,32] . On the contrary Knox-macaulay and co suggested otherwise from their work, stating that there was a statistically significant difference of sTfR values in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Kohgo et al and Allen et al [9,12] in their respective study, even though the former reported lower values and the latter higher sTfR values for each sex, did not find any significant difference in their mean sTfR as also seen in other related studies. [31,32] . On the contrary Knox-macaulay and co suggested otherwise from their work, stating that there was a statistically significant difference of sTfR values in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Serum iron (Fe), ferritin and transferrin (Tf) were determined using the clinical chemistry analyser Cobas 6000 (Roche Diagnostics, Mannheim Germany). Serum sTfR was assayed with the Siemens Healthineers BN prospect Analyzer (reference range 0.4‐1.8 mg/L) and the Cobas 6000 analyzer (Roche) (reference range 1.9‐4.4 mg/L for women and 2.2‐5.0 mg/L for men) . The TSAT was calculated based on the formula TSAT(%)=Fe (mg/L)×70.9/Tf (g/L).…”
Section: Methodsmentioning
confidence: 99%
“…Ferritín reyndist skilvirkari maelikvarði á járnskort en sTfR í þessari könnun. Í öðrum könnunum, þar sem þessar rannsóknir hafa verið bornar saman, hefur sTfR reynst betri en ferritín í sumum 10,16,[21][22][23] en ekki í öðrum, 15,17,18 ef til vill vegna mismunandi þýðis. Kannað var hvort bólgusvörun hefði áhrif á notagildi rannsóknanna með því að athuga naemi, sértaeki og skilvirkni þeirra við greiningu járn-skorts auk maelikvarða Youdens hjá þátttakendum með CRP annars vegar <6 mg/L og hins vegar ≥6 mg/L.…”
Section: Umraeðaunclassified